Association of growth differential factor-15, hs-cardiac troponin T and N-terminal pro-brain natriuretic peptide with coronary artery disease in patients undergoing elective coronary angiography. (14th October 2021) - Souaid, T; Hijazi, Z; Barakett, V; Sarkis, A; Kadri, Z; Batra, G; Lindback, J; Abdelmassih, T; Noujaim, M; Azar, R R
Abstract: Background: Although the importance of conventional risk factors is well established, a significant proportion of patients with coronary artery disease (CAD) lack any of these factors and many patients without CAD have one or more of them. Better tools are needed to improve risk stratification of patients. Purpose: We aimed to investigate the association between plasma levels of growth differentiation factor 15 (GDF-15), a marker of stress and inflammation, high-sensitivity cardiac troponin T (hs-cTnT) and N-terminal pro-brain natriuretic peptide (NT-proBNP) with the presence of CAD in stable patients referred for elective coronary angiography. Methods: Plasma levels of the three biomarkers were measured in 252 consecutive patients. Patients with known CAD, acute coronary syndrome, or with chronic inflammatory conditions were excluded. CAD was defined by the presence of at least one lesion causing >50% stenosis. The outcome was defined as an ordinal variable with 3 levels: no CAD, 1- or 2-vessel CAD and 3-vessel or left main CAD. Results: Median age was 63 years (56–71), and 35% of patients were females. Among conventional risk factors, hypertension was the most prevalent (70%), followed by hyperlipidemia (69%), smoking (42%), diabetes (33%) and family history of CAD (32%). Of the 252 patients enrolled, 153 (61%) had no CAD, 81 (32%) 1- or 2-vessel CAD, and 18 (7%) 3-vessel or left main CAD. Plasma levels of GDF-15, hs-cTnT and NT-proBNP in each of the 3 groups of CAD are summarized in table 1. In unadjusted ordinal logistic regression analysis, GDF-15 and hs-cTnT were statistically significantly associated with the presence and extent of CAD, while NT-proBNP was not (table 1). However, in a multivariable analysis including age, sex and traditional risk factors, the association of GDF-15 and hs-cTnT with angiographic CAD was attenuated and no longer statistically significant. Age, male sex, family history of premature CAD and the presence of hyperlipidemia, were independent predictors of the presence and extent of CAD (table 2). Conclusion: In stable patients referred for coronary angiography, plasma levels of GDF-15 and hs-cTnT could predict the presence of CAD when evaluated separately. However, that association was attenuated by clinical characteristics. FUNDunding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Roche Diagnostics International LtdForrenstrasse 26343 RotkreuzSwitzerland